دور الذكاء الاصطناعي في المؤسسة الناشئة من وجهة نظر الطلبة الجامعيين - جبريط أحمد; عيشوش محمد الحافظ (جامعة الوادي University of Eloued, 2024)
يعتبر الذكاء الاصطناعي ظاهرة تكنولوجية حديثة في عالم الآلة والعالم الرقمي الرهيب ,حيث يقبل الطلبة الجامعيين أصحاب أفكار المؤسسات الناشئة على استخدام تقنيات الذكاء الاصطناعي لتحديد المشكلات وتشخيصها وتحديد الحل الأمثل من بين البدائل المتاحة ,وتهدف هذه الدراسة إلى إبراز دور الذكاء الاصطناعي في المؤسسات الناشئة من خلال معرفة رأي الطلبة الجامعيين وما مدى تقبلهم لهذه التقنيات وتوظيفها في مؤسساتهم الناشئة من خلال بعض المعايير كالملائمة والبحث والتطوير والفعالية اللازمة ,ولقد تمت هذه الدراسة على عينة عشوائية من طلبة جامعة الوادي ضمن تخصصات شعبة التسيير والاقتصاد والتكنولوجيا والبيولوجيا من خلال توزيع الاستبيان ومعالجته ببرنامج spss .v26 ومن بين النتائج المتوصل إليها ما يلي: - أغلب الطلبة الجامعيين كان توجههم الموافقة على تطبيق تقنيات الذكاء الاصطناعي في المؤسسات الناشئة. - لا توجد فروق بين الجنسين من ناحية تطبيق الذكاء الاصطناعي في المؤسسات الناشئة. - هناك رغبة كبيرة في البحث والتطوير لدى الطلبة الجامعيين وخاصة في تطبيق تقنيات الذكاء الاصطناعي من خلال إنشاء المؤسسات الناشئة وهذا ما أظهرته هذه الدراسة من خلال ارتفاع معدل المتوسط العام لهذا المحور من الدراسة. Artificial intelligence is considered a that technological phenomenon in the machine’s world and the terrible digital world. University students with ideas for emerging enterprises accept the technologies artificial intelligence techniques to identify problems and determine the optimal solution from among the available alternatives. This study aims to highlight the role of artificial intelligence in emerging enterprises through... Knowing the opinion of university students and the extent of their acceptance of these technologies and employing them in their emerging institutions through some criteria such as suitability, research and development, and the necessary effectiveness. This study was conducted on a random sample of students from the University of the Valley within the specializations of the Department of Management, Economics, Technology, and Biology, through distributing the questionnaire and processing it with the Spss program. v26, Among the results obtained are the following: - Most of the university students were willing to approve the application of artificial intelligence techniques in emerging institutions. - There are no differences between genders in terms of applying artificial intelligence in emerging institutions. - There is a great desire for research and development among university students, especially in applying artificial intelligence techniques through the establishment of emerging institutions, the this is what this study showed through the high general average rate for this field of study.
The role of artificial intelligence in emerging institutions from the perspective of university students A Case study of El Oued University Students
Keywords: الذكاء الاصطناعي; المؤسسات الناشئة; الطلبة الجامعيين; البحث والتطوير